Audel machine shop basics - Miller, Rex, 1929-2019 (Audel machinist's library., 2004)
Use the right tool the right way. Here, fully updated to include new machines and electronic/digital controls, is the ultimate guide to basic machine shop equipment and how to use it. Whether you're a professional machinist, an apprentice, a trade student, or a handy homeowner, this fully illustrated volume helps you define tools and use them properly and safely. It's packed with review questions for students, and loaded with answers you need on the job. Mark Richard Miller is a Professor and Chairman of the Industrial Technology Department at Texas A & M University in Kingsville, Texas. * Under.